Implementasi Hidden Curriculum Literasi dalam Pembelajaran Daring - Rian Dwiyanto; Hindun Hindun (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Hidden curriculum emphasizes the development of affective aspects and students' self-actualization as a model for achieving learning goals. This research investigates the implementation of a hidden literacy curriculum in an online learning context, with a focus on program preparation, implementation, and completion. The aim of this research is to revive the nation's literacy spirit for Indonesia's future progress. The method used is descriptive with a qualitative approach to describe directly how the situation and implementation process takes place. Through analysis of literacy needs and selection of relevant materials, this program preparation creates a solid foundation. The implementation of this hidden curriculum emphasizes literacy orientation, integrated activities, and individual support to increase student participation and development of literacy skills. Literacy final projects, self-evaluations, and portfolio creation provide concrete evidence of students' literacy achievements, while evaluations of program effectiveness guide subsequent improvements. Overall, this research provides insight into how hidden curriculum literacy can shape students as independent learners who are able to apply literacy in their daily lives.